Model of force calculation of fast and slow motor units of knee extensor muscles in isometric mode - Voronov, A.; Shpakov, A.; Tomilovskaya, E.; Voronova, A.; Sokolov, N. (American Journal of Sports Science, 2026)
Knee extensors are mixed muscles containing both fast (FMU) and slow motor units (SMU). It has been hypothesized that, at high angular velocities (150-360 deg/s), FMU contributes primarily to knee joint moment development, while at low angular velocities (30-120 deg/s), both FMU and SMU contribute to force generation. It was hypothesized that the maximum isometric moment in m. quadriceps, registered on the isokinetic dynamometer "BIODEX System 4Pro"at speeds of 30-150 deg/s, represents the sum of the moments from SMU and FMU, while in the range of 150-360 deg/s, it is primarily generated by FMU. The maximum isometric moment created by the FMU was calculated using a linear equation, as the force-velocity relationship becomes linear at high velocities. During knee extension at a constant angular velocity, the maximum number of RMUs, according to the model, is activated up to an angular velocity of 240 deg/s: (knee amplitude motion 90 deg) / (time developing maximum force 0.37s) = 240 deg/s. The maximum number of MMUs is recruited 1.09 s after the onset of knee extension, which corresponds to an angular velocity of 90 deg/based on the results of isokinetic dynamometry and a mathematical model, FMU and SMU forces were calculated for highly skilled athletes of different sports. For athletes of various specializations, the SMU force does not exceed 24 N/kg, while the FMU force ranges from 52-83 N/kg. The main result of this study demonstrates an acceptable level of agreement between the model and experimental calculations of the SMU and FMU contributions to knee extension force. Based on the obtained model characteristics, individual "boundaries" of SMU and FMU involvement can be determined.